Effects of Superoxide Dismutase and Catalase on Disseminated Intravascular Coagulation In Rats - Yoshikawa, T; Murakami, M; Yoshida, N; Seto, O; Kondo, M (Thrombosis and Haemostasis, 1983)
The effects of superoxide dismutase (SOD) and catalase on endotoxin-induced experimental disseminated intravascular coagulation (DIC) were studied in rats. Experimental DIC was induced by a 4 hr sustained infusion of endotoxin at a dose of 100 mg/kg. The rats were subcutaneously injected with SOD at 0.5, 5.0 or 50.0 mg/kg, or catalase at 0.01, 0.1 or 1.0 mg/kg, followed by the continuously infusion of 100 mg/kg/4hr of endotoxin. A preventive effect against DIC was noted in all the parameters, such as fibrinogen and fibrin degradation products, fibrinogen level, prothrombin time, partial thromboplastin time, platelet count and the number of renal glomeruli with fibrin thrombi, in the rats treated with 50.0 mg/kg of SOD or 1.0 mg/kg of catalase. When 50.0 mg/kg of SOD or 1.0 mg/kg of catalse was injected subcutaneously at 1, 2 or 3 hr after the initiation of the endotoxin-infusion, the protective effect against DIC was noted in all the parameters.
Keywords: Disseminated intravascular coagulation; Endotoxin; Superoxide dismutase; Catalase; Rat